Problems of foreign students at the University of Wisconsin-La Crosse - Dutchin, Winston L. (My University, 1974)
The purpose of this study was to identify the problems of foreign students at the University of Wisconsin-La Crosse. The sample of this study included subjects from Ethiopia, Guyana, Hong Kong, and Nigeria. The results of this investigation included: 1. Foreign students experienced their greatest difficulties in securing personal and college finances. 2. These students had problems adjusting to the food and climate. 3. Foreign students had difficulties obtaining dates. 4. The academic area provided problems for foreign students. These included note-taking, writing papers and preparing for tests. On the basis of the results of this study, recommendations were made for the foreign student advisor and the foreign students. These included that the foreign student advisor explore additional methods of reducing financial hardship, that foreign students be aware of special academic programs in school, and that the immigration laws be explained. Further, foreign students must realize that they came to the United states to obtain higher education and as such had established that they had financial support. Any change in their financial arrangements should not be the burden of the university--rather the cooperation of the university and the students.

Fish, Kennith R.

Zemelis, Andrei
Keywords: Students, Foreign - Wisconsin -- La Crosse; University of Wisconsin--La Crosse -- Students